Application of Diffie-Hellman Algorithm Method (Key-Exchange) in Cryptography - Sagala, Sarah (Sean Institute, 2024)
In cryptography, key exchange security is essential. Because the message code can only be a message that is analyzed with a key offer that matches this message. Secret messages can be delivered through symmetric cryptographic algorithms with coded keys or with key exchange algorithms. One of the key exchange methods that has been developed is Diffie-Hellman Key-Exchange (DHKE). Diffie-Hellman is a simple method used to generate a key between two parties in order to communicate securely. The two parties running this algorithm have their own secret variables, by exchanging two public variable values and performing calculations using the received variables and secret variables obtained randomly shared secret. The security strength in this algorithm can be improved by combining an asymmetric key algorithm, namely RSA. This algorithm is not only in generating RSA keys, but also in calculating discrete logarithms in RSA and Diffie-Hellman. The results of this algorithm are key strength and confidentiality that can be used in symmetric cryptographic algorithms.